Inside Back Cover: Bicyclic Guanidine Catalyzed Asymmetric Tandem Isomerization Intramolecular‐Diels–Alder Reaction: The First Catalytic Enantioselective Total Synthesis of (+)‐alpha‐Yohimbine (Chem. Asian J. 3/2016). Issue 3 (21st January 2016) - Feng, Wei; Jiang, Danfeng; Kee, Choon‐Wee; Liu, Hongjun; Tan, Choon‐Hong
Abstract : A catalytic enantioselective total synthesis of (+)‐alpha‐yohimbine has been demonstrated. Chiral bicyclic guanidine was used to catalyze an enantioselective tandem‐isomerization intramolecular Diels–Alder reaction leading to the formation of hydroisoquinoline derivatives. Enantioenriched alpha‐yohimbine was synthesized from hydroisoquinolines through a nine‐step sequence. The final product was fully characterized and the absolute configuration was confirmed using X‐ray crystalllography. More information can be found in the Full paper by Choon‐Hong Tan et al. onpage 390 in Issue 3, 2016 (DOI:10.1002/asia.201500246 ).